Identification and functional characterization of cardiac troponin I as a novel disease gene in autosomal dominant dilated cardiomyopathy. - Carballo, S; Robinson, P; Otway, R; Fatkin, D; Jongbloed, J; de Jonge, N; Blair, E; van Tintelen, J; Redwood, C; Watkins, H (2009)
RATIONALE: Idiopathic dilated cardiomyopathy (DCM) is inherited in approximately one third of cases, usually as an autosomal dominant trait. More than 30 loci have been identified, several of which encode sarcomeric proteins which can also be mutated to cause hypertrophic cardiomyopathy. One contractile protein gene well known as a hypertrophic cardiomyopathy disease gene, but with no reported mutation in autosomal dominant DCM, is TNNI3 which encodes cardiac troponin I. OBJECTIVE: To test TNNI3 as a candidate gene, a panel of 96 probands with DCM was analyzed. METHODS AND RESULTS: Genomic DNA was isolated and TNNI3 exons screened by heteroduplex analysis. Exons with aberrant profiles were sequenced and variants evaluated by segregation analysis and study of normal controls. We report 2 novel TNNI3 missense mutations, Lys36Gln and Asn185Lys, each associated with severe and early onset familial DCM. Of the 5 mutation carriers, cardiac transplantation was required in 3, at ages 6, 15, and 24 years. Analysis of Ca(2+) regulation of actin-tropomyosin-activated myosin ATPase by troponin revealed that troponin reconstituted with either mutant troponin I gave lower maximum ATPase rates and lower Ca(2+) sensitivity than wild type. Furthermore, mutant thin filaments had reduced Ca(2+) affinity compared with normal. CONCLUSIONS: The functional alterations mirror closely a consistent phenotype found in proven DCM mutations in other thin filament proteins, thus supporting the interpretation that these mutations are disease-causing. These are the first reported autosomal dominant DCM-causing mutations in TNNI3, and so the findings expand the spectrum of disease-causing genes that lead to either hypertrophic cardiomyopathy or DCM depending on the specific mutation.